2007
DOI: 10.1177/0040517507078796
|View full text |Cite
|
Sign up to set email alerts
|

Packing Density of Compact Yarns

Abstract: In this work, fiber distribution through the cross-sections of compact yarns and their packing density values was investigated to provide a better understanding of the internal structures of compact yarns produced by different compact spinning systems, since there is no information available so far regarding their internal structure. The results of packing density analysis indicated that compact yarns had nearly 15—30% higher packing density values compared to that of the conventional ring spun yarns. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 9 publications
2
45
1
Order By: Relevance
“…As shown in Figure 1, on the last radial ring, a few fiber areas were located at a considerably higher distance than that of most of the fibers. 1 So we need to obtain the real yarn diameter as much as possible. The effective yarn diameter D ef obtained from the fiber packing density distribution was considered as the best value representing the real yarn diameter.…”
Section: Evaluation Of Fiber Packing Density In Yarn Cross Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, on the last radial ring, a few fiber areas were located at a considerably higher distance than that of most of the fibers. 1 So we need to obtain the real yarn diameter as much as possible. The effective yarn diameter D ef obtained from the fiber packing density distribution was considered as the best value representing the real yarn diameter.…”
Section: Evaluation Of Fiber Packing Density In Yarn Cross Sectionmentioning
confidence: 99%
“…There are many yarn properties, such as yarn strength, elongation, appearance and compactness, concerned with the fiber arrangement. 1 The early research on fiber packing density had been reported by Schwarz in 1951. 2 Schwarz 2 proposed two systems of packing: one being open packing and the other being close hexagonal packing.…”
mentioning
confidence: 99%
“…Yilmaz, Goktepe, Goktepe, and Kremenakova (2007) have analyzed the effect of type of compact spinning machine on the fiber packing density.…”
Section: Introductionmentioning
confidence: 99%
“…Because textile yarns are neither continuous nor perfectly elastic, in this study, we apply the above definition to the yarns and called it as apparent Poisson's ratio. The relationships between physical properties and both the tensile property and geometry of the cross-section of a yarn have been widely investigated [11][12][13][14][15][16][17][18]27]. Barella [19] measured the yarn diameter under different tensile loads using a projection microscope.…”
Section: Introductionmentioning
confidence: 99%